The viability hedging instruments in current application - Nadhirah, Nordin; Azlin Alisa, Ahmad; Mustafa' Afifi, Ab. Halim (2014)
Hedging method is often associated with derivatives contract. However, the application of derivatives in hedging is facing some arguments and disputes among the jumhur fuqaha (majority Islamic jurists). Therefore, various alternative methods of hedging recommendations have been given by the islamic scholars. Despite these recommendations not all of them can be applied in the current financial industry. Therefore under this study, these recommendations will be divided into 2 categories, the proposed hedging method that is difficult to be applied and the proposed hedging method that can be applied. The study found that among various tools of hedging proposed, the principle of wacd is one of the most relevant and suitable method to be adopted due to its flexiblility and easy application in hedging products.